Analisis Lintasan Berpikir Siswa Dalam Menyelesaikan Soal Cerita Matematika: Studi Kasus Siswa Broken Home SDN 32 Cakranegara - Abdul Rasyid; Mohammad Archi Maulyda; Vivi Rachmatul Hidayati (IJPSE Indonesian Journal of Primary Science Education, 2026)
This study aims to describe the thinking trajectories of students from broken home families in solving mathematical word problems at SDN 32 Cakranegara. This research employed a qualitative approach using a case study method. The research subjects consisted of 20 students from broken home families, with four students selected as the main subjects representing different family conditions: parental disharmony, parental divorce, parental absence, and parental death. Data were collected through written tests and semi-structured interviews. The data were analyzed through stages of data collection, data condensation, data display, and conclusion drawing. The results showed that the thinking trajectories of the four subjects were not fully systematic according to Polya’s problem-solving stages. The subject with parental disharmony was able to follow the thinking trajectory well. The subject with divorced parents experienced difficulties in determining appropriate problem-solving strategies. The subject with parental absence encountered obstacles in carrying out the plan and explaining the solution process. Meanwhile, the subject who experienced parental death had difficulties starting from the stage of understanding the problem, which affected the following stages of problem solving. In general, the obstacles experienced by students were influenced by lack of concentration and limited habits of reviewing final results. This study contributes to enriching literature on mathematical problem solving based on Polya’s stages and can serve as a reference for teachers in designing more effective learning that supports students’ learning needs.